CREATING A WEBSITE IN WORDPRESS: A COMPREHENSIVE GUIDE (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
This paper provides a detailed exploration of the process of creating a website using WordPress, one of the most popular content management systems (CMS) in the world. It examines the essential steps involved in setting up a WordPress website, including domain registration, hosting, installation, theme selection, and customization. The paper also discusses the advantages of using WordPress, such as its user-friendly interface, scalability, and the extensive availability of plugins and themes. Furthermore, it addresses common challenges faced by beginners and offers solutions to overcome them. This guide serves as a practical resource for individuals and businesses aiming to establish a robust online presence.